Análise quali-qualitativa e por meio de sistema de informações geográficas da arborização do quadrilátero central de Ribeirão Preto, SP - Romani, Gustavo de Nobrega [UNESP] (2014)
Vegetation in urban environments is essential as a city quality element, and its proper maintenance reduces disturbances caused by building trade excesses, which removes native woods, changing local microclimate other than flora and fauna biological cycle alterations. Quantitative and qualitative survey of arboreal specimens of cities provides useful data for decision making of afforestation master plans, helping to improve urban environment citizen benefit. Ribeirão Preto city downtown holds great historical and cultural importance, since it was where the city began to grow. In this way, we aimed to conduct a phytosociological and quali-quantitative survey of trees and palms along the streets; and through Landsat TM local maps, detect vegetation growth or decline over the years, and observing possible heat island formations through temperature map analysis. Total tree and palm individuals were 1832 split into 89 species, 72 genera and 35 botanical families. Although the area presents high species diversity, verified by Shannon-Weaver index (3.41), most species are not Brazil-native, in small and medium heights. We observed that the major afforestation problems were related to inadequate pruning, poorly dimensioned planting holes and excessive spacing between plants. There was an average 70% reduction of NDVI of most squares between 1984 and 2011, except for Bandeiras that had 64.29% increase of it. Average temperature in squares was about 1 to 2 °C lower than in the surrounding area until 150-200 meters far. Digital Elevation Model (DEM) can be used in forward square planning of neighborhoods, identifying appropriate locations to set squares, parks and green areas in order to improve water infiltration into the soil without overloading storm drainage system. Although diverse, the afforestation on the central quadrangle needs attention, especially for problems related to tree and palm ...